2022
DOI: 10.21037/atm-22-5920
|View full text |Cite
|
Sign up to set email alerts
|

Electroacupuncture alleviates neuropathic pain caused by spared nerve injury by promoting AMPK/mTOR-mediated autophagy in dorsal root ganglion macrophage

Abstract: Background: Dorsal root ganglia (DRG) plays an important role in mediating the peripheral sensation transduction through the primary afferent neurons in pain research. Neuropathic pain (NP) is a syndrome of hyperalgesia, spontaneous pain and allodynia caused by central or peripheral nerve injury. Recent trends of study are turning towards the development of therapies for the management of NP. Activation of autophagy in glial cells in the spinal cord has been reported to be associated with attenuation of NP, bu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 58 publications
0
4
0
Order By: Relevance
“…Mice assigned to the EA group were treated with 2/100 Hz EA at the bilateral Yanglingquan (GB34) acupoints located between the heads of the tibia and fibula ( Figure 1 A) for 15 min daily from day 7 to day 14 after TNI or sham surgery. This treatment period has been shown to induce a stable antinociceptive effect on neuropathic pain [ 27 , 28 , 29 ]. Constant current square-wave electrical stimulation generated by a HANS acupoint nerve stimulator (HANS-200A, Nanjing Jisheng Medical Technology Co., Ltd., Nanjing, China) was administered via two acupuncture needles.…”
Section: Methodsmentioning
confidence: 99%
“…Mice assigned to the EA group were treated with 2/100 Hz EA at the bilateral Yanglingquan (GB34) acupoints located between the heads of the tibia and fibula ( Figure 1 A) for 15 min daily from day 7 to day 14 after TNI or sham surgery. This treatment period has been shown to induce a stable antinociceptive effect on neuropathic pain [ 27 , 28 , 29 ]. Constant current square-wave electrical stimulation generated by a HANS acupoint nerve stimulator (HANS-200A, Nanjing Jisheng Medical Technology Co., Ltd., Nanjing, China) was administered via two acupuncture needles.…”
Section: Methodsmentioning
confidence: 99%
“…Electroacupuncture (EA) is a promising complementary strategy for neuropathic pain treatment, essentially through the descending inhibitory system and endogenous opioid peptides [ 131 , 132 , 133 , 134 , 135 ], such as β-endorphins, met-enkephalin and dynorphin [ 135 ]. This rehabilitation modality contributes to the upregulation expression of TRVT in the dorsal root ganglia (DRG) and spinal cord [ 131 ]. Xu and colleagues (2022) elucidated the regulation and role of the AMP-activated protein kinase/mammalian target of rapamycin (AMPK/mTOR) signaling pathway.…”
Section: The Problem Of Neuropathic Painmentioning
confidence: 99%
“…Xu and colleagues (2022) elucidated the regulation and role of the AMP-activated protein kinase/mammalian target of rapamycin (AMPK/mTOR) signaling pathway. AMPK/mTOR is involved in triggering autophagy in DRG macrophages, after EA stimulation in rats [ 131 ].…”
Section: The Problem Of Neuropathic Painmentioning
confidence: 99%
“…Acupuncture is an important part of Traditional Chinese Medicine ( 15 , 16 ). It has been reported that acupuncture can reduce the postoperative inflammatory response in patients undergoing lung surgery, thus reducing postoperative pulmonary complications such as cough ( 17 , 18 ).…”
Section: Introductionmentioning
confidence: 99%